(untitled) (Revista Brasileira Multidisciplinar, 2014)
BSTRACT The objective of the present paper is to draw a brief analysis of the ambush marketing, which is a practice adopted by an enterprise that seeks to get an indirect association with a sport, social or cultural event, without being really involved with it, as a way of getting the benefits of exposure assured to the official sponsors. For this purpose, it was used the theoretical-conceptual and descriptive-interpretative methods, by means of the critical interpretation of the main observed aspects concerning the theme. From this point, it was possible to conclude that the referred theme has become more and more relevant because of the growing investments in sponsorship in the so-called "mega events". More than this, it was possible to notice that, regardless the necessity of a better delimitation of the requirements or elements that enable the configuration of "ambush marketing", under the legal perspective, nowadays, Brazil has rules to fight against this practice. As examples, can be mentioned the Civil Code of 2002, that in its article 884 prohibits the unjust enrichment, and the Industrial Property Law (Law nº9.279/96), which enables the protection of the industrial property rights by means of the registration of trade and the repression to unfair competition (article 2º) and through the prevision of the crime of unfair competition (article 195). Doubt remains if, considering the uncertainties that surround the theme, the existing rules will be enough and adequate to restrain ambush marketing.